(3GdeKdK aj GddZIs - (3eMeO Hf jYbhH Hf eMeO, eLO GdOjf GdajQhRGHGOj,J (B817 (3g` s
(3ChdgG (B:s
(3CTQa eG fWb Hg GdeUOY GdeMOK CMeO Gddg Gddg GdPi CZGK YHGOg hHYO jbhd gPG cJGH LeY LejY eG CWdbJ Ydjg ef GdcJH GdehVhYI ai GdeKdK s
(3BNQgG (B:s
(3BNQ GdehLhO efg Hbhdg ai HGH GdhGh (B: (3GdhO GdhJO hHGdcSQ GdNd hHGdVe GSe GdUfe s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B147s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK s
Keywords: (3GddZIs